2008
DOI: 10.1111/j.0906-7590.2008.05456.x
|View full text |Cite
|
Sign up to set email alerts
|

Likely responses of the Antarctic benthos to climate‐related changes in physical disturbance during the 21st century, based primarily on evidence from the West Antarctic Peninsula region

Abstract: Disturbance has always shaped the evolution and ecology of organisms and nowhere is this more apparent that on the iceberg gouged continental shelves of the Antarctic Peninsula (AP). The vast majority of currently described polar biodiversity occurs on the Southern Ocean shelf but current and projected climate change is rapidly altering disturbance intensities in some regions. The AP is now amongst the fastest warming and changing regions on earth. Seasonal sea ice has decreased in time and extent, most glacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 138 publications
1
75
0
1
Order By: Relevance
“…Parts of the Antarctic Peninsula, including the WAP, are already experiencing the greatest increase in mean annual atmospheric temperature on Earth (Chapman and Walsh, 2007;Clarke et al, 2007;Solomon et al, 2007;Smale and Barnes, 2008), and temperatures at the seafloor in the Southern Ocean are predicted to rise by as much as 0.7°C at abyssal depths and 1.7°C at bathyal depths by 2100 ( Table 2). Field and modeling studies have also revealed rapid atmospheric and surface-water warming in the Arctic Ocean during recent decades (Overland et al, 2004;Spielhagen et al, 2011).…”
Section: The Polar Deep Seasmentioning
confidence: 99%
See 1 more Smart Citation
“…Parts of the Antarctic Peninsula, including the WAP, are already experiencing the greatest increase in mean annual atmospheric temperature on Earth (Chapman and Walsh, 2007;Clarke et al, 2007;Solomon et al, 2007;Smale and Barnes, 2008), and temperatures at the seafloor in the Southern Ocean are predicted to rise by as much as 0.7°C at abyssal depths and 1.7°C at bathyal depths by 2100 ( Table 2). Field and modeling studies have also revealed rapid atmospheric and surface-water warming in the Arctic Ocean during recent decades (Overland et al, 2004;Spielhagen et al, 2011).…”
Section: The Polar Deep Seasmentioning
confidence: 99%
“…Large icebergs can scour the sediment down to 400 m on the Antarctic shelf. This disturbance leads to scale-dependent recolonization of scoured areas and an increased input of dropstones (Smale and Barnes, 2008). These processes will enhance seafloor heterogeneity and create hard substrates for sessile megafauna (Schulz et al, 2010;Meyer et al 2015Meyer et al , 2016.…”
Section: The Polar Deep Seasmentioning
confidence: 99%
“…Polar regions are affected by a high level of disturbance associated with iceberg scour and glacial sedimentation (Barnes 1999;Gutt 2001;Smale and Barnes 2008); however, not all aspects of these problems were studied equally in the Arctic and in the Antarctic. While ice scour disturbance was intensively studied in both polar regions (Conlan et al 1998;Gutt and Piepenburg 2003;Brown et al 2004;Conlan and Kvitek 2005;Gerdes et al 2008;Smale 2008a), it was recently emphasized by Smale and Barnes (2008) that studies on benthic communities affected by mineral suspension inflow are still lacking from the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…While ice scour disturbance was intensively studied in both polar regions (Conlan et al 1998;Gutt and Piepenburg 2003;Brown et al 2004;Conlan and Kvitek 2005;Gerdes et al 2008;Smale 2008a), it was recently emphasized by Smale and Barnes (2008) that studies on benthic communities affected by mineral suspension inflow are still lacking from the Southern Ocean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation